Penjualan dan Biaya Operasional terhadap Laba Bersih pada PT. Ricky Putra Globalindo Tbk - Puji Lestari; Rendra Erdkhadifa (Journal of Management and Bussines (JOMB), 2024)
This research aims to examine the influence of sales and operational costs on PT. Ricky Putra Globalindo Tbk 's net profit during that period. The research method used is a quantitative approach with multiple linear regression analysis. The research sample involved 32 quarterly reports of PT. Ricky Putra Globalindo Tbk from 2015 to 2022. The research results showed that sales had a unidirectional or positive relationship and partially had a significant effect on net profit. On the other hand, operational costs have a unidirectional or negative relationship and partially have a significant effect on net profit. Conclusion, the implications of these findings can be used as a strategic basis for companies in managing sales and operational costs to increase financial stability. Keywords: Operational Costs, Net Profit, Sales